Drummondville : essai d’ethnologie urbaine - Genest, Bernard (Ethnologies, 1994)
This article deals with an experiment in urban ethnology undertaken in Drummondville following the completion of an inventory of Quebec heritage in 1982. Realizing that the urban domain had been largely ignored, the seeds of a new project began to take root among specialists attached to the govemment. A pilot project was undertaken by Bernard Genest in downtown Drummondville. Interdisciplinary in nature, the project was never completed; however, in spite of this, the results gleaned from this exercise remain pertinent to the present project.